A HISTORICAL OVERVIEW OF EMERGENCE AND DEVELOPMENT OF SIKH ART IN PUNJAB - Kaur, Sukhandeep; Viranjan, Ram (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Punjab is one of the paramount states in the history of India from its artistic, literary, and historical significance of view, in which Indian culture and sophistication first came to the forefront. Punjab has always been the motherland of sages, incarnations, Gurus, martyrs, and freedom fighters. The contribution of these Sikh Divine master’s to the society cannot be summed up in a few words. However, many writers endowed the principles about the life of these Gurus in their terms as they penned their spiritual, social, and religious perspectives. Hence, art was not deprived of this touch either; many artistic movements made the Sikh religion the subject of their work. Sikh art has been, at its zenith, among the vast arts prospering in the land of Punjab, which brought the unique religious, social, and historical facets of Sikhism with tremendous sincerity and vividness in the exquisite touch of colours. In this paper, an attempt has been made for sharing some of the essential aspects of Sikh art from its birth to its development, which led to some significant sources of Sikh art in the form of Sikh murals, illustrated manuscripts, and portraits of Sikh Gurus, and so on.